2018
DOI: 10.5897/ajar2018.13163
|View full text |Cite
|
Sign up to set email alerts
|

Major biotic maize production stresses in Ethiopia and their management through host resistance

Abstract: Biotic stresses are recently evolving very rapidly and posing significant yield losses of maize production in Ethiopia. A number of high yielding maize hybrids, initially developed as tolerant/resistant, have been taken out of production due to their susceptibility to major maize diseases. Furthermore, recent disease and insect pest epidemics have clearly shown the importance of breeding maize for biotic stresses and study the genetics of resistance to the major maize disease pathogens, insect pests and parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 72 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Despite the importance of the crop for national food security and as a source of income, the national average yield is 3.6 ton ha −1 which is low compared to the world average of 5.6 ton ha −1 [5]. The low national average yield of the crop is attributed to biotic and abiotic stresses, poor management and low use of inputs [6,7]. Among abiotic stresses, climate change in terms of increasing temperature, decreasing rainfall, and variability were found to have a great impact on maize production [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the crop for national food security and as a source of income, the national average yield is 3.6 ton ha −1 which is low compared to the world average of 5.6 ton ha −1 [5]. The low national average yield of the crop is attributed to biotic and abiotic stresses, poor management and low use of inputs [6,7]. Among abiotic stresses, climate change in terms of increasing temperature, decreasing rainfall, and variability were found to have a great impact on maize production [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports by Gidi (2023) and Keno et al (2018) indicated that integrated disease management has clearly demonstrated moderate levels of HPR when combined with field treatment and affordable levels of chemical control, and expected yields and economic returns are higher than those obtained from chemical control of susceptible genotypes. The present experiment also revealed that maize varieties sprayed with Mancozeb combined with host resistance significantly reduced the incidence, severity, progression rate, and AUDPC of CLR disease compared to the control plot.…”
Section: Discussionmentioning
confidence: 99%
“…This dependence decreases as grain approaches maturity. Keno et al (2018) reported that in Ethiopia, inbred lines BH546, BH547, and BH661 were identified to possess genes resistant to foliar diseases, including gray leaf spot disease and TLB. Similarly, four maize genetically similar lines were discovered as potential sources of resistance to gray leaf spot disease in Ethiopia, which could be beneficial to farmers and breeding programs (Bekeko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meteorological data show that Ethiopia has experienced increasing temperatures over the past 38 years (Belay et al, 2021). These changes are compromising production of cereal crops, and maize is among those most affected (Keno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%